UTILIZATION OF AUGMENTED REALITY IN DEVELOPING LEARNING MEDIA ON OPTICAL MATERIAL - Rajo Hasim Lubis; Irfandi Irfandi; Budiman Nasution (UNIVERSITAS NEGERI MEDAN, 2022)
Industrial revolution-based learning media 4.0 is urgently needed when it is in accordance with technological developments. The purpose of this research is to see the effectiveness of learning media based on Augmented Reality in learning. The research subjects were computer science study program students in the General Physics course, the type of research used was Research and Development (R&D) by applying the 4D model. The data collection technique used in this study was an assessment instrument with a questionnaire. Data analysis techniques were carried out to obtain good quality products that meet the aspects of validity, practicality and effectiveness. Based on the results of the study, it was obtained that AR-based learning media on material with special lens rays was valid, practical and effective so that it was concluded that it was feasible to use in learning